Overexpression of heat shock protein 27 (HSP27) increases gemcitabine sensitivity in pancreatic cancer cells through S‐phase arrest and apoptosis. Issue 2 (21st October 2014) - Guo, Yang; Ziesch, Andreas; Hocke, Sandra; Kampmann, Eric; Ochs, Stephanie; De Toni, Enrico N.; Göke, Burkhard; Gallmeier, Eike
Abstract We previously established a role for HSP27 as a predictive marker for therapeutic response towards gemcitabine in pancreatic cancer. Here, we investigate the underlying mechanisms of HSP27‐mediated gemcitabine sensitivity. Utilizing a pancreatic cancer cell model with stable HSP27 overexpression, cell cycle arrest and apoptosis induction were analysed by flow cytometry, nuclear staining, immunoblotting and mitochondrial staining. Drug sensitivity studies were performed by proliferation assays. Hyperthermia was simulated using mild heat shock at 41.8°C. Upon gemcitabine treatment, HSP27‐overexpressing cells displayed an early S‐phase arrest subsequently followed by a strongly increased sub‐G1 fraction. Apoptosis was characterized by PARP‐, CASPASE 3‐, CASPASE 8‐, CASPASE 9‐ and BIM‐ activation along with a mitochondrial membrane potential loss. It was reversible through chemical caspase inhibition. Importantly, gemcitabine sensitivity and PARP cleavage were also elicited by heat shock‐induced HSP27 overexpression, although to a smaller extent, in a panel of pancreatic cancer cell lines. Finally, HSP27‐overexpressing pancreatic cancer cells displayed an increased sensitivity also towards death receptor‐targeting agents, suggesting another pro‐apoptotic role of HSP27 along the extrinsic apoptosis pathway. Taken together, in contrast to the well‐established anti‐apoptotic properties of HSP27 in cancer, our study reveals novel pro‐apoptotic functions of HSP27—mediated through both the intrinsic and the extrinsic apoptotic pathways—at least in pancreatic cancer cells. HSP27 could represent a predictive marker of therapeutic response towards specific drug classes in pancreatic cancer and provides a novel molecular rationale for current clinical trials applying the combination of gemcitabine with regional hyperthermia in pancreatic cancer patients.